Teaching interpreting in times of Covid: perspectives, experience and satisfaction - Castillo-Rodríguez, Cristina Milagrosa; Toledo-Báez, María Cristina; Seghiri-Domínguez, Míriam (Universitat Politècnica de València, 2023)
Technological tools have complemented face-to-face instructions at university from the beginning of the 21st century. However, COVID-19 pandemic forced many faculty members to switch rapidly, and without any specific training, to an emergency remote teaching. The aim of this paper is to analyse the impressions of Spanish faculty members teaching interpreting in an online mode. A total of 65 faculty members answered a semi-structured online survey, covering the 80.8% of all the Spanish universities where interpreting subjects are taught. The results revealed some pitfalls derived mainly from the lack of physical issues (booth, body language evaluation), absence of human contact, lack of suitable technology, more teaching hours, cognitive load, lack of concentration, and students monitoring. However, the benefits detected were more self-practice, more attendance to sessions, and the preparation of students for a remote interpreting, taking into account that this will be the future of professional language interpreting practice.
Keywords: Enseñanza - Innovaciones tecnológicas; Tecnología educativa; Interpreting; Teaching experience; Teaching satisfaction; Online teaching; Remote teaching